Prescribing pattern of oral Non-Steroidal Anti-Inflammatory Drugs (NSAIDS) at Out-Patient Department in Hospital Sultanah Bahiyah, Alor Setar - Kamaludin, Noor Irfan; Meor Zamri, Wan Nur Farahain (2011)
Objective: The main objective of this study was to evaluate the prescribing pattern of NSAIDs among practitioners. Methodology: This prospective study was carried out in the outpatient pharmacy in Hospital Sultanah Bahiyah, Alor Setar. The duration of study was three months, from July 2010 to September 2010. Prescriptions containing orally prescribed NSAIDs were obtained using e-HIS and analysed into our data collection form. Results: It showed that NSAIDs were most widely prescribed for post delivery or caesarean and abortion with approximately quarter of the prescriptions collected. This was closely followed by traumatic injury, musculoskeletal pain and arthritis. The least prescribed indication was for pelvic inflammatory disease which accounted for 6.2 percent of the prescriptions. In point of department, Orthopaedic most frequently prescribed NSAIDs, followed by Obstetrical and Gynaecology and the least came from Pathology. It was also found that most of the prescriptions were for patients between 31 to 60 years old which is 1312. The number of females was almost doubled compared to males which are 2220 and 1157 respectively. Among the races, Malays formed the largest group, followed by Indian, Chinese and others. Conclusion: This study gave a general idea of the prescribing pattern of NSAIDs in HSB prescribed by doctors. Future studies may include the duration of prescriptions and their costeffectiveness.